Development of assessment instrument business proposal for students' systems thinking skills on business model canvas in bioentrepreneurship course - Lulu Desia Mutiani Rahmayuni; Siti Sriyati; Diah Kusumawaty (University of Muhammadiyah Malang, 2024)
Business Model Canvas (BMC) is a business model that must be mastered by students in the Bioentrepreneurship course as an initial provision for entering the entrepreneurial world, while in compiling Business Model Canvas (BMC) systematic thinking skills are needed. This study aims to provide an assessment instrument to measure students' system thinking skills in Business Model Canvas (BMC) material. The method used in this research is exploratory mixed method with exploratory sequential design stages. The participants involved were 40 students of Biology study program who contracted Bioentrepreneur course in one of the universities in Bandung City. The instrument was developed in the form of an assessment rubric with 29 indicators of systems thinking skills in Business Model Canvas. The quality of the instrument with validity based on expert judgment obtained a value of 89.3% with a very valid category, and the quality of the instrument with inter-rater reliability based on Cronbach's Alpha value obtained a value of 0.762 to 1.000 which is categorized as very good. Students' system thinking skills can emerge and be measured in the creation of a Business Model Canvas (BMC) in a business proposal by using the developed assessment instrument. So that the novelty in this study is that the assessment instrument of students' system thinking ability in making Business Model Canvas is declared valid and feasible for use in Bioentrepreneurship courses.